PERAN PREVENTION OFFICER DALAM PENGURANGAN BIAYA PADA BISNIS ECERAN - PURNOMO, CHRISTIEN AULIA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
In variety of business can’t be separated from the loss. Including retail business. Many retailers suffered losses due to various factors. In many cases retail business could be loss, either criminal or non criminal causes doing by internal or external person/ organization. The losses could make a higher in operational cost for retailer. The knowledge of risk management could so useful for retailer. Finally retailer could make efficiency in operational cost and increase the profit otherwise can press it down the crime in competition of the retailer. The crime anticipation can prevented by prevention officer program.